Role of ACTH in the Interactive/Paracrine Regulation of Adrenal Steroid Secretion in Physiological and Pathophysiological Conditions - Lefebvre, Hervé; Thomas, Michaël; Duparc, Céline; Bertherat, Jérôme; Louiset, Estelle (Frontiers in Endocrinology, 2016)
In the normal human adrenal gland, steroid secretion is regulated by a complex network of autocrine/paracrine interactions involving bioactive signals released by endothelial cells, nerve terminals, chromaffin cells, immunocompetent cells and adrenocortical cells themselves. ACTH can be locally produced by medullary chromaffin cells and is therefore a major mediator of the corticomedullary functional interplay. Plasma ACTH also triggers the release of angiogenic and vasoactive agents from adrenocortical cells and adrenal mast cells, and thus indirectly regulates steroid production through modulation of the adrenal blood flow. Adrenocortical neoplasms associated with steroid hypersecretion exhibit molecular and cellular defects which tend to reinforce the influence of paracrine regulatory loops on corticosteroidogenesis. Especially, ACTH has been found to be abnormally synthesized in bilateral macronodular adrenal hyperplasia responsible for hypercortisolism. In these tissues, ACTH is detected in a subpopulation of adrenocortical cells which express gonadal markers. This observation suggests that ectopic production of ACTH may result from impaired embryogenesis leading to abnormal maturation of the adrenogonadal primordium. Globally, the current literature indicates that ACTH is a major player in the autocrine/paracrine processes occurring in the adrenal gland in both physiological and pathological conditions.